A K‐Means Clustering Analysis of the Jovian and Terrestrial Magnetopauses: A Technique to Classify Global Magnetospheric Behavior. Issue 9 (11th September 2020) - Collier, Michael R.; Gruesbeck, Jacob R.; Connerney, John E. P.; Joy, Steven P.; Hospodarsky, George B.; Roberts, Aaron; Sibeck, David G.; Roelof, Edmond C.
Abstract: Previous studies suggested that the Jovian magnetopause position is best characterized as a bimodal distribution indicative of a two‐state system. We applied a modified k ‐means clustering analysis to observations of the Jovian and terrestrial magnetopause crossings. Clustering analysis using pre‐Juno data shows that the Jovian magnetopause is best described as a two‐state system, whereas the terrestrial magnetopause is best described by a single state, indicating that the behavior of the Jovian magnetopause is fundamentally different from that of the terrestrial magnetopause. We also analyzed magnetopause locations detected by the Juno spacecraft and conclude that their distribution is consistent with a two‐state system. The origin of the different number of Jovian and terrestrial magnetopause states may be due to the disparate source strengths supplying the two magnetospheres. The Jovian magnetosphere is supplied with about a metric ton of Iogenic heavy ions per second, whereas the terrestrial source, Earth's ionosphere, is two orders of magnitude weaker. A suggestive correlation between Io phase and magnetopause state may be consistent with this proposed link between an internal source and a two‐state magnetopause. The possible role of energetic magnetospheric events and Jovian current systems is discussed. Plain Language Summary: A new analysis technique shows that the region dominated by Jupiter's magnetic field, Jupiter's magnetosphere, has two distinct states, a compressed and an inflated state. This is in contrast to Earth's magnetosphere, which has only a single state, and suggests that Jupiter's magnetopause position is influenced by internal processes. This technique provides a method to classify magnetospheres based on observations of only their boundary surfaces and suggests that some of their internal properties can be inferred by these observations. Key Points: K ‐means clustering classifies global magnetospheric behavior Analysis confirms that Jovian magnetopause position is bimodal Analysis confirms that terrestrial magnetopause position is monomodal